Magnetoencephalography insights to dementia and drug intervention. (1st February 2022) - Hughes, Laura E.; Adams, Natalie E.; Phillips, Holly; Murley, Alexander G.; Shaw, Alexander; Nesbitt, David; Cope, Thomas E.; Bevan‐Jones, W. Richard; Passamonti, Luca; Rowe, James B.
Abstract: Background: Magnetoencephalography (MEG) is a promising tool for experimental medicine in dementia, and a core technology for the Dementias Platform UK. It quantifies in vivo human network and synaptic physiology, with high‐dimensional data at a millisecond time‐scale. Its proven sensitivity to neurodegenerative disease has applications in diagnostics and early detection, mechanistic studies of pathogenesis, and biomarkers to accelerate clinical trials and evidence target engagement. Here, we build on recent work with Serotonin and GABA‐ergic modulation, to illustrate MEG insights into the neurophysiological effects of the NMDA receptor antagonist Memantine. We use Frontotemporal dementia and Progressive supranuclear palsy (bvFTD, PSP) as demonstrator conditions in view of their focal glutamatergic deficits. Method: 24 Patients with bvFTD and PSP, and 20 healthy controls underwent magnetoencephalography, 7T MRI spectroscopy and a battery of cognitive tests in a double‐blind placebo‐controlled crossover design, using Memantine 10mg/Placebo. We test the relationship between cortical oscillations, baseline glutamate concentration and response to pharmacological intervention. Result: Neurophysiological activity was impaired in patients, with diminished low frequency oscillations and disrupted cortical connectivity. These abnormalities correlated with reduced baseline glutamate concentration. Memantine enhanced the neuronal response, particularly in prefrontal regions. Conclusion: MEG provides insights into targetable pathophysiological effects of neurodegeneration and markers for treatment studies. It is sensitive to disease and individual differences in pathophysiology, reliable, safe, well‐tolerated and sufficiently scalable for early phase trials. MEG evidence of selective neuronal dysfunction and network reorganisation can couple with microcircuit models for synaptic assays, or be used directly as a readout for interventional studies. MEG is ideally suited to support both academic and pharma initiatives, with quantitative tools for early phase clinical trials, illustrated here with Memantine, but applicable to other compounds.